Evaluation of oxygen concentrators for use in countries with limited resources. (8th May 2013) - Peel, D.; Neighbour, R.; Eltringham, R. J.
Summary Seven different models of oxygen concentrators were purchased. The manufacturer's data were evaluated by a ranking method for operation at high temperature and high relative humidity, power consumption, warranty and cost. Measurements were then made of the oxygen concentration produced at maximum operating temperature. All the concentrators were CE marked and claimed compliance with the relevant Standard ISO 8359:1996. Only two models complied with their specification. On examination of the concentrators and the accompanying documents we found that compliance with 61 points listed in ISO 8359 ranged from 85% to 98%. Oxygen concentration was measured with the machines running simultaneously under both high temperature and high humidity. All models delivered low oxygen concentrations at 40 °C and 95% relative humidity. Only two models delivered > 82% at 35 °C and 50% relative humidity. Concentrators intended for use in countries with limited resources should be evaluated before they are purchased, by independent experts, using the methods described herein.